Penerapan Hak Ex Officio Hakim dan Asas Ius Contra Legem dalam Perkara Perceraian dan Pembagian Harta Bersama di Pengadilan Agama Magetan Perspektif Hukum Progresif - Zainal Faizin; Ahmad Junaidi (Journal of Economics, Law, and Humanities, 2022)
Throughout 2019 the Magetan Religious Court has decided on divorce cases accompanied by the distribution of joint assets in four cases. From the four cases, legal dynamics emerged in their decisions, namely regarding the use of ex officio rights with reference to statutory regulations and the application of the principle of ius contra legem in deciding cases. The focus of the study in this thesis is the application of the ex officio rights of judges and the principle of ius contra legem in the case of sharing assets in the Magetan Religious Court with a progressive legal perspective. The approach used in this research is the progressive legal approach, which studies how the law is applied and whether it is in accordance with the principles of justice that make law for humans. Meanwhile, the theory used is a legal discovery with the characteristics of progressive law. Whereas the use of ex officio rights by applying the principle of ius contra legem solely aims to protect the legal interests of justice seekers by using the spirit of progressive law which is based on the legal interests of justice seekers which must be put forward rather than merely referring to codified rules, however, the judges do not abandon the legal principles which form the basis of the judges' thinking and actions in examining, hearing and deciding cases.